Effect of Nanocrystalline Diamond Films Deflection on Wear Observed in Reciprocating Sliding Tests - Podgursky, V.; Bogatov, A.; Sobolev, S.; Viljus, M.; Sedov, V.; Ashkinazi, E. (Journal of Coating Science and Technology, 2016)
The present study deals with the tribological behavior of nanocrystalline diamond (NCD) films. The diamond films were deposited by microwave plasma enhanced chemical vapor deposition (MPCVD) in methane/hydrogen/air plasma on the Si(100) substrates. The tribological properties were studied by reciprocal sliding tests against Si3N4 balls. The depth profiles and surface morphology of the wear scars were investigated by means of mechanical profilometry and scanning electron microscopy (SEM). Various adaptation processes occur between contacting surfaces including asperity polishing, formation of carbonaceous tribolayer and ripple patterns on the wear scar surfaces. The film deflection is the specific form of adaptation decreasing contact pressure and, therefore, the damage (including wear) of both counter bodies. The deflection of NCD films in sliding tests can be related with the effect of fatigue.